Economic Growth from the Household Perspective GDP and Income Distribution Developments Across OECD Countries - Causa, Orsetta (OECD Economics Department Working Papers, 2014)
This paper provides an assessment of how households' income has fared compared with GDP. While the prime focus is on incomes around the median, attention is paid also to the bottom of the income distribution. Thus, one contribution of the paper is to deliver a fresh assessment of the evolution of inequality and poverty across OECD countries over the last fifteen years. The analysis relies on a rich array of indicators, producing new evidence of the various patterns of differences in income distributions across countries and over time. For example, it assesses the extent to which stability in overall income inequality masks compensating changes between the lower and upper halves of the income distribution. Also, it explores whether contracting inequalities coexist with increasing poverty. The paper adds to previous studies by introducing, measuring and analysing income polarisation in a cross-country comparative perspective. Distinguishing polarisation from inequality and comparing their evolution over time provides new policy-relevant perspectives on the nature of the changing income distribution